2012
DOI: 10.1021/om300061d
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Phosphaferrocene–Pyrrole–Phosphaferrocene P-N-P Pincer Ligand

Abstract: A 2-ethoxycarbonylphosphaferrocene was reduced to the corresponding 2-hydroxymethyl derivative, which was condensed with pyrrole in a 2:1 ratio in the presence of BF 3 to give a phosphaferrocene−pyrrole−phosphaferrocene pincer ligand. This tridentate ligand, in turn, reacted with [Rh(acac)(CO) 2 ] to yield a rhodium carbonyl pincer complex. This complex was characterized by X-ray crystal structure analysis and tested in the hydroformylation of internal olefins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…The formation of 2 from bis (dimethylaminomethyl)pyrrole occurs in higher yield than that for 1 presumably due to the increased nucleophilicity of the secondary alkyl phosphine. 31 P NMR spectra of 2 display a single peak at −7.67 consistent with trivalent phosphorus. 33 Similar to compound 1 , no J HP coupling is observed between the methylene protons of the pincer “arms” and the phosphorus nuclei by 1 H NMR spectroscopy (see Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…The formation of 2 from bis (dimethylaminomethyl)pyrrole occurs in higher yield than that for 1 presumably due to the increased nucleophilicity of the secondary alkyl phosphine. 31 P NMR spectra of 2 display a single peak at −7.67 consistent with trivalent phosphorus. 33 Similar to compound 1 , no J HP coupling is observed between the methylene protons of the pincer “arms” and the phosphorus nuclei by 1 H NMR spectroscopy (see Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…The closely related PyrPhos (PNP)H, which forms six‐membered chelates upon coordination to a metal ion (shown for Rh I ), has so far only appeared in a single publication. This may be due to its greater stereochemical complexity: Its isolation was reported in the form of an equimolar rac/meso ‐mixture limiting its usefulness as a general structural motif . However, it was shown that the larger six‐membered chelate rings are readily integrated into a pincer structure, provided the central pyrrole motif is twisted significantly to allow for meridional complexation .…”
Section: N‐heterocyclic Pnp Pincers: An Overviewmentioning
confidence: 99%
“…This may be due to its greater stereochemical complexity: Its isolation was reported in the form of an equimolar rac/meso ‐mixture limiting its usefulness as a general structural motif . However, it was shown that the larger six‐membered chelate rings are readily integrated into a pincer structure, provided the central pyrrole motif is twisted significantly to allow for meridional complexation . This inclusion of six‐membered chelate rings into pincers was further established by the preparation of CbzC ( R PNP)H in 2013 – formally by introducing two methylene units into the rigid Cbz ( R PNP)H platform .…”
Section: N‐heterocyclic Pnp Pincers: An Overviewmentioning
confidence: 99%
“…最近他们又报道了利用化合物 66 合成新型 P-N-P 型 Rh 的钳形配合物 70 (Eq. 2), 并考察了其在烯烃氢甲 酰化反应中的应用 [43] . C=P 键(-10.3 eV)能级的巨大差异 [44] , 而无法有效的 协同为一个 P,N-双齿配体与金属进行配位.…”
Section: Scheme 19unclassified